Aerodynamic characteristics and structural behavior of sound barrier under vehicle-induced flow for five typical vehicles. (February 2023) - Wang, Dalei; Sun, Mengjin; Shen, Xiang; Chen, Airong
Abstract: Running vehicles cause disturbances in the surrounding air, which lead to a vehicle-induced aerodynamic load (VIAL) on roadside thin-wall structures. In this study, to reveal the aerodynamic load mechanism on roadside sound barriers subjected to the action of a vehicle-induced airflow, the Computational Fluid Dynamics(CFD) method is used to simulate the airflow around a running vehicle and adjacent to the sound barrier. First, the reliability of the numerical simulation is verified by comparing it with field tests. Second, using the CFD method, flow fields around the running vehicle with and without a sound barrier are obtained, the wind-pressure distribution is extracted, and the micro-mechanism of the sound barrier's influence on the airflow around the running vehicle is revealed by comparing and analyzing the flow-field distribution characteristics. Thirdly, through parametric studies, the changing rules of the wind-pressure distribution and the VIAL effect of internal force on the sound barrier screen are presented under different conditions, i.e., sound barrier height, vehicle shape, vehicle–barrier separation distance, and sound barrier shape. Then, using the FEM method, the load effect of vehicle-induced airflow on the sound barrier column is revealed. The conclusions improve the understanding of the action mechanisms of the vehicle-induced airflow on roadside sound barriers.